A stretchable and hydrophobic polypyrrole/knitted cotton fabric electrode for all-solid-state supercapacitor with excellent strain capacitance. (20th February 2019) - Wang, Bo; Song, Weihua; Gu, Peng; Fan, Lihua; Yin, Yunjie; Wang, Chaoxia
Abstract: As a promising energy storage and supply device, supercapacitor (SC) has attracted much attention recently. In this work, polypyrrole/knitted cotton fabric (PKCF) electrodes with flexibility and stretchability have been fabricated through a facile in-situ polymerization method to enrich the application of SC in wearable electronic devices. Due to the rough structure, the obtained PKCF exhibits good hydrophobicity with static water-contact-angle about 135°. PKCF-15 electrode (the amount of pyrrole monomer in the initial polymerization system is 15 g or 50 g L −1 ) is optimized by a comprehensive consideration about conductivity and specific capacitances, which shows areal capacitances of 481 mF cm −2 at 5 mV s −1 and 1433 mF cm −2 at 1 mA cm −2, respectively. Due to the structural changes of fabric substrate, the obtained PKCF-15 performs a resistivity downtrend and improved capacitance with course strain increasing. The areal capacitances of symmetric all-solid-state supercapacitor (ASSSC) based on PKCF-15 are 101 and 450 mF cm −2 at 5 mV s −1 and 1 mA cm −2, respectively. The devices assembled by different course stretching PKCF-15 also display excellent strain capacitances, suggesting a promising electrode candidate for wearable energy devices.